Improving Hazard Identification, Risk Assessment and Risk Control (HIRARC) Implementation in Industrialized Building System (IBS) Construction Projects - Rosman, Muhamad Farhan Nur Ariff; Jabar, Izatul laili; Yusof, Mohd Reeza (Research in Management of Technology and Business, 2023)
The hazards for conventional construction methods are different from the hazards for Industrialised Building system (IBS) construction methods. The differences are due to the distinct construction method applied, however the consideration for safety for both methods are crucial to ensure the project success. In order to decrease the likelihood of accidents occurring on the IBS construction projects, the hazards, risk and their preventive measures must be taken into account. Therefore, the objectives of this paper is to identify the current implementation of Hazard Identification, Risk Assessment and Risk Control (HIRARC) during the IBS construction and to recommend the improvement of safety level on IBS construction using HIRARC. A quantitative approach by means of questionnaires is carried out, the questionnaires are distributed to the IBS constractors in Klang Valley area. It is found that most activities in the HIRARC are moderately applied in IBS construction and the improvement based on HIRARC have been recommended in order to improve the safety. The findings of this paper is perceived to assist the construction companies in understanding and implementing the HIRARC during the IBS construction project.